2009
DOI: 10.4314/ejesm.v2i1.43497
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Granite Quarrying on the Health of Workers and Nearby Residents in Abeokuta Ogun State, Nigeria

Abstract: The present paper monitored levels of suspended particulate matters in the ambient air in and around selected quarries and analyzed the prevalent health problems suffered by nearby residents and quarry workers. It also assessed the residents' awareness of the negative implications of living in close proximity to quarry sites. Suspended Particulate Matter (SPM) meter was employed to monitor the level of particulate matter (PM 10 ) within and around five quarry sites selected for this study. The data collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 7 publications
3
50
1
2
Order By: Relevance
“…The lifting of heavy stones during loading and offloading of vehicles also caused muscle pain among many quarry workers. About 26.7% of the respondents complained of cough/asthma [8,7, them complained of eyes a result of the continued presence of dust during quarrying and particulate matter in the air caused by big stone transportation trucks [9,8,7,6] and destruction of vegetation cover [6]. of the respondents complained of malaria.…”
Section: Fig 5 Income Per Month From Stone Quarrying For Community mentioning
confidence: 99%
See 2 more Smart Citations
“…The lifting of heavy stones during loading and offloading of vehicles also caused muscle pain among many quarry workers. About 26.7% of the respondents complained of cough/asthma [8,7, them complained of eyes a result of the continued presence of dust during quarrying and particulate matter in the air caused by big stone transportation trucks [9,8,7,6] and destruction of vegetation cover [6]. of the respondents complained of malaria.…”
Section: Fig 5 Income Per Month From Stone Quarrying For Community mentioning
confidence: 99%
“…Further the operations in stone quarrying, whether small or large-scale, are inherently disruptive to the environment, producing enormous quantities of waste that can have deleterious impacts for decades and that the environmental deterioration caused by stone quarrying occurs mainly as a result of inappropriate and wasteful working practices and rehabilitation measures [3,4]. For instance, some studies in the Northern Region of Ghana and East Gonja District in particular found that commercial extraction of sand and gravel cause land degradation and desertification through destruction of economically important trees mostly indigenous in nature [5,6]. This degradation of environment due to stone quarrying activities has put forth questions as to whether or not the mining activities should be continued [7,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were similarities in the health problems suffered by the residents living near quarry sites and quarry workers in the study area. [13] In Delhi, India, no personal protective equipment was provided to quarry workers, helmets, safety belts, masks, safety shoes were "foreign" things. [14] People should not work in a quarry unless they are competent based on knowledge, experience, training and other qualities related to the job they are to do.…”
mentioning
confidence: 99%
“…The data obtained from each location will be plotted between distance and air quality level. [6] Reports studied began from the year 1995 to 2002 and it contains the assessment, prevention and reducing method of the impact for environment. [7] Table 2 shows the relationship between distances of residency and the quarrying impact of affected respondent.…”
Section: Analysis Of Document Review On Quarryingmentioning
confidence: 99%